Analisis Kemampuan Komunikasi Matematis Pada Pembelajaran Matematika Berdasarkan Aspek Norma Sosiomatematik - Samsul Maarif; Laras Indah Mayowi (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2023)
The study aims to determine students’ mathematical communication skills in learning mathematics based on aspects of sosiomathematic norms. This research methotd uses descriptive qualitative. The subjects in this study were 6 students who were selected based on their level, namely high, medium and low. Researchers used questionnaires, test questions, and interviews with the aim of knowing the extent to which subjects had mathematical communication skills and sociomathematical norms. Then, data analysis techniques used the Rasch model on questionnaires and test questions, the during interviews used data reduction analysis, data collection, and drawing conclusions using the MAXQDA application. The results of this study are: a) students who have a high level of mathematics communication ability have high sociomathematic norms as well as medium and low levels; b) the characteristics of students mathematical communication abilities are more towards indicators of writing and mathematical expression; c) the characteristics of students sociomathematics norms lead to indicators of mathematical differences and mathematical insights. The research can be a source of information and reference for readers.